2011
DOI: 10.1111/j.1365-313x.2011.04554.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis metacaspase 2d is a positive mediator of cell death induced during biotic and abiotic stresses

Abstract: SUMMARYCysteine proteases such as caspases play important roles in programmed cell death (PCD) of metazoans. Plant metacaspases (MCPs), a family of cysteine proteases structurally related to caspases, have been hypothesized to be ancestors of metazoan caspases, despite their different substrate specificity. Arabidopsis thaliana contains six type II MCP genes (AtMCP2a-f). Whether and how these individual members are involved in controlling PCD in plants remains largely unknown. Here we investigated the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 45 publications
(66 reference statements)
5
105
0
1
Order By: Relevance
“…Both MC9 gain-of-function or loss-of-function plants did not display any obvious aberrant phenotypes under normal vegetative or reproductive growth conditions. MC4 expression was the highest (Figure 1G), consistent with a previous report that it is the most expressed metacaspase at various growth stages (Watanabe and Lam, 2011a). In young seedlings, corresponding to a developmentally active stage with a dynamic proteome, the MC9 expression was the second highest; therefore, this stage was chosen for analysis of the MC9 degradome ( Figure 1G).…”
Section: Expression Characteristics Of the Arabidopsis Mc9 Genesupporting
confidence: 86%
“…Both MC9 gain-of-function or loss-of-function plants did not display any obvious aberrant phenotypes under normal vegetative or reproductive growth conditions. MC4 expression was the highest (Figure 1G), consistent with a previous report that it is the most expressed metacaspase at various growth stages (Watanabe and Lam, 2011a). In young seedlings, corresponding to a developmentally active stage with a dynamic proteome, the MC9 expression was the second highest; therefore, this stage was chosen for analysis of the MC9 degradome ( Figure 1G).…”
Section: Expression Characteristics Of the Arabidopsis Mc9 Genesupporting
confidence: 86%
“…Loss of the predominant type II metacaspase in Arabidopsis, AtMC4, has been found recently to compromise cell death induction by the fungal toxin fumonisin B-1 (FB1), an incompatible bacterial pathogen, and chemical inducers of oxidative stress in seedlings. 32 This work has further shown that AtMC4 processing from its zymogen is accelerated during activation of cell death by these agents, consistent with its deduced role in orchestrating PCD under these conditions. Lastly, a type I metacaspase AtMC1 was shown to be a positive regulator of the HR cell death in Arabidopsis, whereas another type I metacaspase, AtMC2, was found to counteract this pro-cell death effect of AtMC1 (see also review by Coll et al, in this issue).…”
Section: Metacaspases In Cell Deathsupporting
confidence: 51%
“…2 During the past decade, experimental evidence in multiple species using reverse-genetic methods have supported type-II MCPs as positive mediators of PCD. [3][4][5] Among the 6 type-II MCPs in Arabidopsis, the nomenclature of which has recently been unified, 2 AtMC8 was found to be involved in UV-C and oxidative stress-induced PCD while the catalytic activity of AtMC4 is demonstrated to be essential for its in planta function during oxidative stresses as well as toxininduced PCD. 4,5 Among the three type-I MCPs in Arabidopsis, two of them were recently shown to antagonistically modulate PCD with the anti-death function of AtMC2 being independent of its catalytic activity.…”
Section: Mcps-conserved Cell Death Regulators In Plantsmentioning
confidence: 99%
“…[3][4][5] Among the 6 type-II MCPs in Arabidopsis, the nomenclature of which has recently been unified, 2 AtMC8 was found to be involved in UV-C and oxidative stress-induced PCD while the catalytic activity of AtMC4 is demonstrated to be essential for its in planta function during oxidative stresses as well as toxininduced PCD. 4,5 Among the three type-I MCPs in Arabidopsis, two of them were recently shown to antagonistically modulate PCD with the anti-death function of AtMC2 being independent of its catalytic activity. 6 Based on these new data, it is appropriate to state that MCPs are important cell death regulators in plants, especially under induced-stress scenarios.…”
Section: Mcps-conserved Cell Death Regulators In Plantsmentioning
confidence: 99%